A scoping review on emerging biomarkers in inflammatory bowel disease: Towards precision medicine in diagnosis and therapeutic management - Matheus Querino da Silva; João Daniel de Souza Menezes; José Luis Esteves Francisco; Franciane Michele da Silva; Paula Camile Vieira Rocha; Paula Buck de Oliveira Ruiz; Caroline Cristina dos Santos Costa; Laís Fernanda de Amorin; Clarissa Albuquerque Vaz Nunes; Nilton Sebastião Garcia de Almeida Neto; Lorena Aline dos Santos; Guilherme Ribeiro Constancio; et al. (PLoS ONE, 2026)
Background Inflammatory Bowel Diseases (IBD) are chronic conditions presenting significant diagnostic and management challenges. Current invasive methods and traditional biomarkers often lack sufficient accuracy and fail to address the disease’s heterogeneity and unpredictable therapeutic responses. This necessitates more precise, personalized clinical tools. Methods This scoping review synthesized recent findings on emerging biomarkers for IBD. We focused on technological advances in omics platforms (genomics, transcriptomics, proteomics, metabolomics, microbiomics), artificial intelligence, biosensors, and imaging techniques. Analysis identified biomarker potential for early diagnosis, disease activity monitoring, progression prognosis, and therapeutic response prediction. The review adhered to PRISMA-ScR guidelines and was registered with the Open Science Framework (OSF). The search encompassed five major databases: PubMed/MEDLINE, Scopus, Web of Science, Embase, and Google Scholar. Results Studies demonstrate vast potential in non-invasive biomarkers for refined early diagnosis, optimized disease monitoring, and treatment response prediction. Key findings include metabolomic and gut microbiota profiles, genetic and epigenetic markers, and AI integration of complex data. These approaches promise to overcome conventional indicator limitations. From 784 initial records, 27 articles were included, published between 2021 and 2025. Conclusion Emerging biomarkers are fundamental for the transition to precision medicine in IBD. Their implementation aims to enhance pathogenesis understanding, personalize therapies, and improve patient quality of life, establishing pathways for more effective, individualized management approaches.